Reconstructing peatland water tables using transfer functions for plant macrofossils and testate amoebae: A methodological comparison - Väliranta, M.; Blundell, A.; Charman, D.J.; Karofeld, E.; Korhola, A.; Sillasoo, Ü.; Tuittila, E.-S. (Quaternary international, 2012)
Relatively seldom is the same parameter reconstructed from the same site using different proxies, resulting in a persistent problem for palaeoecological studies whereby a reconstruction based on a single-proxy may provide an unequivocal view of the changes in past conditions. Plant macrofossils and testate amoebae are commonly used proxies to reconstruct past changes in peatland surface moisture conditions, but there are no comparisons between quantitative reconstructions based on both techniques. This paper compares two high-resolution late-Holocene quantitative water table (WT) reconstructions based on transfer functions for plant macrofossils and testate amoebae from two boreal peatland sites in Finland and Estonia. The reconstructed WT variation patterns during the last ca. 5000 years are almost identical in directions for both proxies. However, both bog records contain one inconsistent episode when the two proxies indicate different hydrological conditions. In both cases, the testate amoebae reconstruction shows wetter than the average conditions, whereas the plant-based reconstruction indicates drier than the average conditions. Several, possibly simultaneously affecting, reasons can be suggested for mismatches between proxies: 1) the proxies have different response times and sensitivities to hydrological changes, 2) the species-ecology is inadequately known, 3) the modern analogues are poor, 4) the microhabitat dynamics are unpredictable, and 5) the modern data set is too small. Divergences between the proxy records emphasize the fact that single-proxy reconstructions are subject to larger uncertainties than those based on two or more methods.